The Gaze of the Soul and of the Angel in the Renaissance Philosophy of Marsilio Ficino - Uršič, Marko (Ars et humanitas, 2015)
The Renaissance rediscovered the soul as the focus of the universe. Marsilio Ficino calls the soul the "bond of the world" (copula mundi), because it connects the earth and the heaven, immanence and transcendence, time and eternity. On the other hand, the centre of the world becomes more and more relative during the Renaissance period, and individual souls live more and more in their particular times and spaces. In Renaissance paintings, a soul's point of view is determined by perspective, as developed by Masaccio, Fra Angelico, Piero della Francesca et al., and the very position of the eye also features as a "symbolic form" (Erwin Panofsky). However, above each individual and "mobile" soul there are the wings of the "motionless" angel: super animam mobilem est immobilis angelus, as Ficino says in his renaissance Christianity, in reviewing the Platonic-Gnostic myth of the omnipresent angelic gaze. In the archetype of the angel Ficino perceives a metaphor for the all-knowing Intellect, towards which the human soul ascends. Following the iconology of Ernst Gombrich, this paper also takes notice of the influence of Ficino's philosophy on Botticelli's paintings.
Keywords: angel; Ficino, Marsilio, 1433-1499; Botticelli, Sandro, 1444-1510; soul; symbolic form; angeli; duša; simbolne forme; renesančna filozofija; renesančna arhitektura; renesančna umetnost